PENGARUH INTELECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sitti Muliana (AkMen JURNAL ILMIAH, 2015)
Intellectual capital Effect on Financial Performance of the Banking Companies listed on the Stock Exchange Indonseia. This study aimed to analyze the effect of Intellectual capital components namely: value added capital employed, value added human capital, structural capital value added simultaneously affect the financial performance to financial performance. Data was obtained from the documentation of the financial statements of listed companies on the Stock Exchange with the following criteria: banking companies listed in Indonesia Stock Exchange since 2009, and published financial statements for two consecutive years (2009 and 2010). The number of samples in this study were as many as 26 companies. This study uses multiple linear regression analysis, which was preceded by the analysis of the classical assumption, test for normality, multicollinearity, and autocorrelation test, as well as heteroscedasticity test. Based on the hypothesis testing can be concluded as follows: The results of independent variables (Value Added Capital Employed, Value Added Human Capital, Structural Capital and Value Added) on the dependent variable (Return on Assets) indicates that the variable Value Added Capital Employed, Value Added Human Capital, Structural Capital Value Added together or simultaneously positive and significant (at the 5% error level) on the financial performance of 0.280 or 28%.